Capacity building as an effort to achieve organizational sustainability in Kalurahan Imogiri - Bikorin Bikorin; Idam Wahyudi; Anggun Sulistyowati (Universitas Pendidikan Indonesia, 2025)
Kalurahan Imogiri is a non-profit organization that aims to seek optimal welfare for all community members. This Kalurahan has potential and value, but there are many limitations and obstacles in its management, so capacity building efforts are needed. Based on the background and problems faced by partners, AKPRIND University Indonesia is here to help provide solutions. Addressing these challenges requires literacy and an understanding of capacity-building efforts to achieve organizational sustainability. The service method involved providing literacy materials, which was carried out using presentation techniques. At the end of the session, a Focus Group Discussion (FGD) was held to discuss the dynamics of capacity building efforts. Pamong Kalurahan Imogiri was very enthusiastic about following the presentation of the material, and the result was that the pamong began to understand the importance of capacity building efforts. Furthermore, they can identify various problems effectively and recognize the potential of the village to maximize its economic value. It is hoped that after this service activity is carried out, the village will produce appropriate outcomes, providing real and sustainable benefits to the community. Abstrak Kalurahan Imogiri merupakan lembaga non-profit yang mempunyai tujuan untuk mengupayakan kesejahteraan yang optimal bagi seluruh warga masyarakat. Kalurahan ini memiliki potensi dan nilai, tetapi banyak keterbatasan dan hambatan dalam pengelolaanya sehingga dibutuhkan upaya peningkatan kapasitas. Berdasarkan permasalahan yang dihadapi oleh mitra, Universitas AKPRIND Indonesia hadir berpartisipasi membantu memberikan solusi untuk mengatasi permasalahan. Dalam mengatasi permasalahan tersebut, diperlukan upaya literasi dan pemahaman mengenai upaya capacity building guna mewujudkan sustainability organizational. Metode pengabdian yang dilaksanakan berupa pemberian materi literasi. Kegiatan ini dilaksanakan dengan teknik presentasi, berikutnya pada akhir sesi dilaksanakan focus group discussion (FGD) mengenai dinamika dalam upaya peningkatan kapasitas. Para Pamong Kalurahan Imogiri sangat antusias mengikuti pemaparan materi yang disampaikan, hasilnya para pamong mulai memahami bagaimana pentingnya upaya peningkatan kapasitas. Selanjutnya mampu mengidentifikasi berbagai permasalahan dengan baik dan mampu mengidentifikasi potensi kalurahan untuk memaksimalkan nilai ekonomi. Harapannya setelah terlaksana kegiatan pengabdian ini, Kalurahan dapat menghasilkan luaran yang tepat guna untuk memberikan manfaat yang nyata dan berkesinambungan bagi masyarakat. Kata kunci: berdaya; kalurahan; organisasi keberlanjutan; pengembangan kapasitas